Native and non-native ornamental aquarium fishes of Bangladesh - Ishrak Hossain; ABM Mohsin (Universitas Muhammadiyah Malang, 2021)
The study was conducted in Dhaka, Bangladesh. It was carried out for twelve (12) months from March 2018 to February 2019 to prepare a complete update checklist of native and non-native aquarium fishes of Bangladesh. During the current study, 270 varieties (230 freshwater, 36 marine, and 4 brackish water) belong to 149 species (109 freshwater 73 %, 36 marines 24 %, and 4 brackish water 3 %) of 38 families under 10 orders and 6 crossbreeds’ varieties were recorded. Considering the number of species maximum 83 (55.70 %) was found under the order Perciformes followed by Cypriniformes 24 (16.10 %), Characiformes 18 (12.08 %), Siluriformes 11 (7.38 %), Osteoglossiformes 05 (3.35 %), Atheriniformes 03 (2.01 %), Lepisosteiformes 02 (1.34 %), Polypteriformes 01 (0.6 %), Myliobatiformes 01 (0.67 %) and Cyprinodontiformes 01 (0.67 %). The top five popular species were guppy (13.16 %) followed by goldfish (12.39 %), molly (8.54 %), angelfish (6.23 %), platy (5.93 %). The number of fish species' increasing tendency was 5.96 times in the last 15 years, and 3.31 times in the last ten years. Local farms and aquarists breeders bred 76 varieties under 23 species due to its high demand and profitability. Pricing varied on varieties, species, size, and breeding status (local or abroad), availability, and ranged from BDT 40.00-80,000.00 per pair. According to the findings, aquarium fisheries are highly profitable and will be a potential sector in Bangladesh.